Practices of Citizenship in East Africa Perspectives from Philosophical Pragmatism - Holma, Katariina; Kontinen, Tiina (Routledge Explorations in Development Studies, 2020)
Practices of Citizenship in East Africa uses insights from philosophical pragmatism to explore how to strengthen citizenship within developing countries. Using a bottom-up approach, the book investigates the various everyday practices in which citizenship habits are formed and reformulated. In particular, the book reflects on the challenges of implementing the ideals of transformative and critical learning in the attempts to promote active citizenship. Drawing on extensive empirical research from rural Uganda and Tanzania and bringing forward the voices of African researchers and academics, the book highlights the importance of context in defining how habits and practices of citizenship are constructed and understood within communities. The book demonstrates how conceptualizations derived from philosophical pragmatism facilitate identification of the dynamics of incremental change in citizenship. It also provides a definition of learning as reformulation of habits, which helps to understand the difficulties in promoting change. This book will be of interest to scholars within the fields of development, governance, and educational philosophy. Practitioners and policy-makers working on inclusive citizenship and interventions to strengthen civil society will also find the concepts explored in this book useful to their work.